Fabrication Of Titania Nanotubes By A Modified Hydrothermal Method - M.S, Meor Yusoff; M, Masliana M; Paulus, Wilfred; Devi, Parimala; Mahmoud, Mahdi E. (Journal of Science and Technology, 2010)
The main setback of the fabrication of titania nanotubes by the hydrothermal method is the long dissolution time and the usage of highly concentrated NaOH. Our group has managed to develop a modified hydrothermal process that is capable of fabricating titania nanotubes in a shorter timespan while using a more dilute NaOH solution. The study shows that the titania nanotubes starts to form from 7 hours of dissolution, and more nanotubes is produced as the dissolution duration is extended. Similarly, we are able to produce titania nanotubes from a more dilute NaOH solution than those reported earlier. By varying the parameters of the fabrication process, different nanostructures can be obtained such as single, branched nanowires and nanobelts.